Prevalence and determinants of incomplete or not at all vaccination among children aged 12–36 months in Dabat and Gondar districts, northwest of Ethiopia: findings from the primary health care project. Issue 12 (8th December 2020) - Atnafu, Asmamaw; Andargie, Gashaw; Yitayal, Mezgebu; Ayele, Tadesse Awoke; Alemu, Kassahun; Demissie, Getu Debalkie; Wolde, Haileab Fekadu; Dellie, Endalkachew; Azale, Telake; Geremew, Bisrat Misganaw; Kebede, Adane; Teshome, Destaw Fetene; et al.
Abstract : Objective: Ethiopia is one of the Africa's signatory countries for implementation of the primary healthcare strategy including immunisation. In Ethiopia, however, 16% of child death is due to vaccine-preventable disease. Thus, this study aimed to assess the prevalence and determinants of incomplete or not at all vaccination among children aged 12–36 months in Dabat and Gondar districts, Northwest Ethiopia. Study design: The study is community-based cross-sectional study. Study setting: Dabat and Gondar Zuria districts, Northwest Ethiopia. Participants: Mothers/caregivers with children aged 12–36 months were enrolled in the study. Participants were randomly selected through systematic sampling and a total of 603 participants were included in the analysis. Methods: A binary logistic regression analysis was done. In the multivariable logistic regression analysis, a p value of <0.05 and adjusted OR (AOR) with 95% CI were used to identify statistically associated factors with incomplete or not at all vaccination. Outcomes: Incomplete or not at all vaccination. Results: The prevalence of incomplete or not at all vaccinated children was 23.10% (95% CI 16.50 to 29.70). The multivariable analysis revealed that the odds of incomplete or not at all vaccination were higher among mothers who had no antenatal care (ANC) visit (AOR: 1.81, 95% CI 1.21 to 4.03) and no postnatal care (PNC) visit (AOR=1.52, 95% CI 1.05 to 2.25). Conclusions: In the study area, nearly one-fourth of children are incompletely or not at all vaccinated. Our finding suggests that ANC and PNC visits are key determinants of incomplete or not at all vaccination. Thus, in low-resource settings like Ethiopia, the health system approaches to improved ANC and PNC services should be intensified with more effective advice on child immunisation to reduce vaccine preventable disease.